The relationship between violence to children and violence to animals - An ignored link? - Boat, Barbara W. (Journal of interpersonal violence, 1995)
The association between violence to children and violence to animals remains largely unacknowledged in the child abuse/neglect arena. Several reasons justifying further exploration of this link are discussed, along with suggestions for enhancing our awareness, knowledge, and services